Methods of Choosing an Optimal Portfolio of Projects - Yakovlev, A.; Chernenko, M. (University of Miskolc, 2016)
This paper presents an analysis of existing methods for a portfolio of project optimization. The necessity for their improvement is shown. It is suggested to assess the portfolio of projects on the basis of the amount in the difference between the results and costs during development and implementation of selected projects and the losses caused by non-implementation or delayed implementation of projects that were not included in the portfolio. Consideration of capital and current costs components are required for the portfolio of projects efficiency calculation. An optimization model for a portfolio of projects is developed. Consideration of social and economic factors that contribute the integral assessment of the portfolio of project and methods for their calculation are proposed.
Keywords: project; portfolio; economic evaluation; reallocation of resources; interim results; comprehensive studies; probabilistic factors